The development of problem solving-based lifestyle module and its effectiveness on diabetes risk score, random capillary blood glucose and perception in practicing healthy lifestyle among diabetes high-risk group in Kelantan - Mahmud, Munirah (2023)
Background: Diabetes high-risk groups are at intermediate stage in developing type 2 diabetes mellitus (T2DM) but are still reversible. A structured lifestyle education that empowers self-care in lifestyle modifications must be tailored to high-risk groups. Objectives: To develop a problem-solving-based lifestyle education and determine its effect on diabetes risk score (FINDRISC), capillary blood glucose (CBG), and perception practising five healthy lifestyle tasks using MySTAR among diabetes high-risk population in Kelantan. Module satisfaction was assessed among the intervention group participants at post-intervention. Methods: There are two phases of this study. Phase one is the development of the module and phase two is a quasi-experimental study. Based on the literature review and expert discussions, problem-solving based lifestyle education module was developed. Materials include narrated lectures, self-care and simulated counselling videos. Twelve experts evaluated the content validity index (CVI) and 20 community members assessed face validity index (FVI). The intervention group was from the community in Bachok, while the control group was in from Tumpat, who received usual health education from their clinic. The FINDRISC diabetes risk score, CBG and perceived confidence in practising MySTAR tasks were collected pre-and post-8 weeks intervention among 80 diabetes high-risk participants. Module satisfaction questionnaire was given to the intervention group post-intervention. Diabetes risk score was compared using RM ANOVA, while CBG and MySTAR tasks were compared using RM ANCOVA between groups overtime. For each analysis, intention-to-treat (ITT) and per-protocol (PP) analysis were performed. Results: The problem-solving-based lifestyle module was named STOP & SLIMS module, consisting of 17 narrative educational videos, four self-care videos, and twoweekly healthy eating and active lifestyle challenges. Three subcomponents of the module; introduction of prediabetes, healthy eating, and active lifestyle, showed high CVI (90.4%, 88.1%, and 90.2% respectively) and high FVI, ranging from 0.88 to 1.0. Out of 80 participants, 31 participants in the intervention group and 33 in the control group completed the study. There was no significant difference in FINDRISC diabetes risk score between the groups after 8 weeks of intervention. CBG was not significantly different in ITT but significant in PP analysis between the group. In the comparison of groups, the intervention group showed a significantly higher score of perceived confidence to practice MySTAR tasks with adjusted mean difference [95% Confidence Interval (CI)] by doing moderate-intensity exercise 150 minutes per week [15.25 (3.45, 27.05)] and regular physical activity at least three times per week [18.00 (8.14, 27.85)]. Meanwhile, at post-intervention, there were significant differences in mean scores of perceived practising "Suku Suku Separuh" [15.00 (1.82, 28.17)], avoid consume sweet food and beverages [19.15 (8.20, 30.09)], moderateintensity exercise 150 minutes per week [31.41 (18.44, 44.39)] and regular physical activity at least three times per week [28.44 (15.35, 41.53)] between the groups. The intervention group also had high mean satisfaction score for the module ranging from 4.3 to 4.7. Conclusion: The STOP & SLIMS module has the potential to be delivered, particularly to diabetes high-risk groups in order to improve their healthy lifestyle practising, particularly healthy eating and active lifestyle.